PNEUMOCOCCAL INFECTION IN CHILDREN AND ADULTS IN THE POSITION OF A SPECIALIST - Козар, Марія (SWorldJournal, 2023)
Pneumococcal infection is the cause of such diseases as pneumonia, otitis, meningitis, and sometimes even fatal consequences. The best prevention of this disease is specific immunization against pneumococcal vaccine. Specialists do not always have inform